2011
DOI: 10.1093/eurjhf/hfr094
|View full text |Cite
|
Sign up to set email alerts
|

Baseline left ventricular dP/dtmax rather than the acute improvement in dP/dtmax predicts clinical outcome in patients with cardiac resynchronization therapy

Abstract: AimsThe maximum rate of left ventricular (LV) pressure rise (dP/dt max ) has been used to assess the acute haemodynamic effect of cardiac resynchronization therapy (CRT). We tested the hypothesis that LV dP/dt max predicts long-term clinical outcome after initiation of CRT. Methods and resultsThis was a retrospective observational multicentre study in 285 patients in whom dP/dt max was measured invasively following implantation of a CRT device. The minimum required follow-up was 1 year. We analysed the relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 38 publications
2
50
0
1
Order By: Relevance
“…This study investigated acute hemodynamic improvement although these effects may not (completely) translate into chronic outcome. 30 However, the GREATER-EARTH trial reported no differences in reverse remodeling between pacing modalities after 6 months, suggesting that acute similarities may persist into the chronic phase. …”
Section: Limitationsmentioning
confidence: 99%
“…This study investigated acute hemodynamic improvement although these effects may not (completely) translate into chronic outcome. 30 However, the GREATER-EARTH trial reported no differences in reverse remodeling between pacing modalities after 6 months, suggesting that acute similarities may persist into the chronic phase. …”
Section: Limitationsmentioning
confidence: 99%
“…Acute response may not always predict chronic outcome. 24 Moreover, the dog models may not recapitulate all characteristics of dyssynchronous heart failure and LBBB occurring in patients. The canine model used is representative of nonischemic LBBB hearts in patients, but may not reflect all abnormalities present in patients with ischemic hearts.…”
Section: Limitationsmentioning
confidence: 99%
“…In any case, it remains unclear whether a response to early surrogate testing would identify the chronic responders to CRT with respect to hard clinical end points [25]. This reasoning is in line with another report that described how the acute improvement in dP/dt max was not correlated to the clinical outcome, although dP/dt max , measured at baseline and during CRT, was a predictor of 1-year survival free from mortality, heart transplantation, or LV assist device implantation [26]. Thus, it might be that the acute response in contractility, in our study as well as in other studies, might have been a measure of response to CRT than an indicator of prognosis per se.…”
Section: Discussionmentioning
confidence: 84%